Comparison of Different Weed Control Technology Programs - D. E. Peterson; C. Thompson; C. L. Minihan (Kansas Agricultural Experiment Station Research Reports, 2017)
The development of glyphosate-resistant weeds has greatly complicated weed control in soybeans. Roundup Ready 2 Xtend and Liberty Link soybeans provide an alternative postemergence herbicide options for weed control in soybeans. Liberty Link and Roundup Ready 2 Xtend programs provided better overall weed control and slightly higher yields than Roundup Ready 2 Yield programs in this experiment. Yields of Roundup Ready 2 Yield soybeans were likely influenced by more weed competition and possibly crop injury from spray tank contamination by dicamba. Dicamba injury from tank contamination to Roundup Ready 2 Yield soybeans decreased with each subsequent treatment and also with time. At soybean maturity, injury from dicamba tank contamination was no longer evident.
Keywords: Roundup Ready 2 Yield; Roundup Ready 2 Xtend; Liberty Link; soybeans; Palmer amaranth; velvetleaf; morningglory